2022
DOI: 10.3390/ma15228120
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Biological Activity of PEO-Coated Titanium Implants with Conjugates of Cyclic RGD Peptide with Amino Acid Bisphosphonates

Abstract: Titanium is considered to be the most essential metal in the field of implantology. The main factors determining metal biocompatibility, among others, include the morphology and chemical composition of the titanium surface. Therefore, the aim of this work was to develop approaches to control the biological activity of the titanium surface by creating coatings that combine both an inorganic phase with a given morphology and organic molecules containing an integrin-selective peptide that regulate cell adhesion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…If the values of the criterion K p are >1, then plastic contact is realized between the body and the counterbody, regardless of the load [20][21][22][23][24][25]. In our case, the values of the Williamson-Greenwood criterion (8) for all samples after PENC and the raw reference are >1 (Table 1). Thus, the contact is considered plastic and the stress on the contact is taken equal to the hardness, i.e., P r ≈ HB.…”
Section: Contact Stiffness Calculationmentioning
confidence: 53%
See 1 more Smart Citation
“…If the values of the criterion K p are >1, then plastic contact is realized between the body and the counterbody, regardless of the load [20][21][22][23][24][25]. In our case, the values of the Williamson-Greenwood criterion (8) for all samples after PENC and the raw reference are >1 (Table 1). Thus, the contact is considered plastic and the stress on the contact is taken equal to the hardness, i.e., P r ≈ HB.…”
Section: Contact Stiffness Calculationmentioning
confidence: 53%
“…Technologies for plasma-electrolytic treatment have found applications in applying protective ceramic coatings onto the surfaces of metals of the valve group, polishing metal surfaces, and forming hardened diffusion layers on steel and titanium alloys [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…When a capacitor is omitted from the circuit, no current can flow because, when the capacitor is charged, the current will not pass, and the circuit will be cut off. The dense oxide layer on the surface of the titanium also has this effect and, such as a capacitor after being fully charge, disrupts the electrical circuit by reducing the corrosion rate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Based on the EIS diagrams and the obtained data, it can be concluded that the corrosion resistance of the sample with plasma electrolytic oxidation coating is better than that of the uncoated sample.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, these include colloidal forms of metal silicates, as they have the necessary properties as well as good biological compatibility [ 18 , 19 , 20 , 21 , 22 ]. One can distinguish calcium silicate in the crystalline phase—wollastonite, due to its optimal physicochemical and antibacterial properties, as well as its ability to bind bone tissues [ 23 , 24 , 25 ]. In addition, nanosized calcium silicate is excellent for filling teeth, acting as an effective biologically active material [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%